Student acculturation journey: cultural intelligence and acculturation among Malaysian students in France - Mohd. Agusalim, Ardini Marisya; Wan Mohtar, Wan Ikhlas (University of Malaya, 2024)
The understanding of cultural intelligence in France is significant to develop deep comprehension and appreciation of the French language, enabling effective cross-cultural communication and engagement in the French-speaking world. Despite existing studies in cultural intelligence development little is known about Malaysian-French cultural adaptation and acculturation. In response to this gap, this research elaborates on the development of Malaysian-French cultural intelligence and explores the changes in the acculturation process for acquiring cultural intelligence among Malaysian students in France. A total of 60 Malaysian students completed the 39 items E-CQS (Extended Cultural Intelligence Scale). Results showed that the stay enhanced high motivational CQ along with metacognitive CQ, cognitive CQ, and behavioural CQ. There was a significant correlation between language proficiency and student CQ. However, there was no correlation between students' period of residency in France and cultural intelligence level. Interestingly, participants demonstrated the highest CQ score in the dataset resided in France for a short duration. The findings of this study have shown the importance of the positive acculturation journey of Malaysian students in demonstrating an excellent level of CQ, as supported by findings indicating that the quality of exposure to diverse cultural environments is more influential than the duration of residency in the host country.